ASPEK PSIKOLOGI PENDIDIKAN DALAM PEMILIHAN BAHAN BACAAN SASTRA ANAK - IRWANDI, IRWANDI (Pelita Bangsa Pelestari Pancasila, 2016)
Selecting an appropriate text is one of important steps in teaching children literature. Thus, it is needed a scientific consideration especially based on the concept of educational psychology. As an applied psychology, educational psychology concerns on understanding of learning and teaching process and provides certain concepts to help education practitioners in solving learning and teaching problems. The concept of educational psychology is applicable for children literature teaching. This article discusses theoretically and practically the dimension of educational psychology in selecting text for teaching children literature in elementary school. Such dimension encompasses children development in terms of cognition, moral, personality, language, and story concept.